Development of motor learning implementation for ischemic stroke: finding expert consensus - Umi Budi Rahayu; Samekto Wibowo; Ismail Setyopranoto (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2017)
The main purpose of this study was to investigate motor learning implementation forischemic stroke from experts on the field of motor learning in stroke patients includingthe neurologist, medical rehabilitation specialists and physiotherapists. To collect thedata and answer the research questions, statements were made on the basis of thestudy of literature and the grains exploration of the statements in the questionnaire usingthe Delphi Method. Formulation development model was based iteration or judgmentof experts. Validation assessment statement grain tested by the Content Validity Ratio(CVR) and Content Validity Index (CVI) was used to analyze the data. The finding clearup that CVR value of each item statement was 1 and the value of CVI also 1. There were6 indicators in a 26-point declaration on the implementation of the development model ofmotor learning intervention for ischemic stroke. Six indicators included basic theories thatsupport the importance of intervention motor learning, motor learning stages, principlesof motor learning, dosage, timing of and kinds of motor learning interventions that can beprovided as well as application development intervention model motor learning, allowinggiven for ischemic stroke. In conclusion, based on the content validity of the results ofthe consensus expert judgments are six indicators of the importance of motor learningapplication for ischemic stroke.